A atualidade do cosmopolitismo kantiano: a ideia de paz perpétua e o republicanismo em Kant - Cavalcante, Antônio Rodrigues (2022)
The idea of republicanism as a possibility for a "perpetual peace" in Kant's practical philosophy has as its basic foundation the law and the moral duty. For Kant republicanism is the means to achieve a lasting peace, but it depends on a commitment to freedom; therefore peace is for him a moral duty that can only be manifested in law, politics and ethics. The autonomy of the will is the basis of this moral duty, founded on practical reason and the categorical imperative, under which human action is guided by the norms of universal principles shared in common by citizens and the federated states. Kantian republicanism is founded on a constitution that presupposes a law which should ensure, among other things, and above all, that states do not promote war, without their citizens being able to decide upon this subject. The law is the power that should ensure peace between citizens and between the states that take part in the federation of states by means of the coercive means established by their constituent parliamentary assemblies. The force of moral action, resulting from the acceptance of the laws governing the federation of free nations, is the means by which perpetual peace can be guaranteed, as it contains "power", that is, the free decision to act according to duty by obeying to the laws established by the citizens themselves who submit to them. In this dissertation we show that for Kant the law governing the federation acquires the dimension of a moral imperative and ceases to be merely coercive in so far as in the republic the law is the result of a free choice of the citizens themselves, while, in itself, the law remains a guideline that can be fulfilled by mere coercion of the state as a means for guaranteeing peace.